Attract-and-kill and other pheromone-based methods to suppress populations of the Indianmeal moth (Lepidoptera: Pyralidae) - Campos, Manuel; Phillips, Thomas W. (My University, 2014)
Three attract-and-kill formulations, a gel, a wax panel, and a plastic cylinder were tested in simulated warehouses at three densities of devices and at three densities of moths, Plodia interpunctella Hübner, per room. Wax panels and the cylinder formulations suppressed all the densities of moths with only one device per room. Two field experiments were then conducted during 2005 and 2006 in replicated commercial pet food and grocery stores that harbored natural populations of P. interpunctella. In the summer of 2005, the wax panel formulation suppressed adult male response to monitoring traps and also reduced the numbers of larvae in food bait oviposition cups after the first month of being established. This suppression was maintained until the third month. The second field experiment in 2006 compared three pheromone-based methods of moth suppression in buildings with moth populations in untreated buildings. The mass-trapping treatment showed the lowest adult moth capture after the first month of the experiment until the end of the third month. However, this treatment was similar statistically to use of attract-and-kill panels, mating disruption, and untreated control establishments in most of the weeks. Monitoring of larvae in food cups revealed the pheromone-based methods were not significantly different from each other, but that they suppressed moth populations in most of the weeks when compared with untreated control buildings. This research shows potential for successful pheromone-based suppression methods for Indianmeal moths in commercial applications.
Citation: Campos, Manuel, and Thomas W. Phillips. 2014. “Attract-and-Kill and Other Pheromone-Based Methods to Suppress Populations of the Indianmeal Moth (Lepidoptera: Pyralidae).” Journal of Economic Entomology 107 (1): 473–80. https://doi.org/10.1603/EC13451.
Keywords: Stored product; Attracticide; Male annihilation; Mating disruption; Pyrethroid